Pengaruh Motivasi Dan Disiplin Terhadap Kinerja Karyawan (Studi Kasus Pada CV. Indobatu Makmur Palembang) - Erwin Budi Setyawan (STIE Pariwisata API Yogyakarta, 2018)
This study aims to determine how much influence motivation and work discipline on employee performance on CV. Indobatu Makmur Palembang. The variables in this study consisted of independent variables Motivation (X1) and work discipline (X2), and Performance dependent variables (Y). The sample in this study was obtained by survey research. To obtain and collect information from respondents using a questionnaire (structured questionnaire) that is structured according to needs. The method of data analysis uses descriptive statistical analysis. The individual characteristics of the respondents included gender, age, education level and work period. Statistical analysis uses inferential statistics using multiple regression models. To find out the relationship between variables used a correlation coefficient, while to find out the effect used a partial test (t test) and a simultaneous test (F test). From the results of the descriptive statistical analysis on the characteristics of the respondents obtained the percentage of sex: male (93%) and female (7%), percentage of age: <31 years (46%), 31-35 years (33%), 36- 40 years (13%), 41-45 years (8%). Percentage of education level: High School (88%), D3 (8%), S1 (4%). Percentage of service: 6-7 years (14%), 3-5 years (20%), <2 (66%). From the results of the regression analysis, Y increased by 0.397 for each addition per unit variable X1, and Y increased by 0.089 for each addition per unit of variable X2. The effect of variables X1, X2 on Y on the partial test (t test) is on the variable X1 t count = 0.001 <α = 0.05 then there is an influence between motivation on performance. At X2 t count = 0.504 <α = 0.05 then there is a significant effect of motivation and work discipline variables on performance.